Profil Cemaran Bakteri Coliform pada Minuman Susu Segar yang Dijual Pedagang Kaki Lima di Daerah Istimewa Yogyakarta - Charis Amarantini; Tri Yahya Budiarso; Regina Suryanto (Biota : Jurnal Ilmiah Ilmu-Ilmu Hayati, 2005)
Coliform contamination emerges public health case particularly by pathogenic E.coli O157 which is characterized by hemorrhagic colitis with diarrhea. In order to study the profile of coliform bacteria contamination in fresh milk that was sold by the sidewalk trader in Yogyakarta province, in this research coliform detection was done by cultivate fresh milk samples on the medium of Chromocult Coliform Agar (CCA) and enrichment cultures on the medium of Vancomycin-Trypticase Soy Broth (mVTSB). Dark-blue colonies isolated on CCA plates were then evaluated for the ability to ferment D-sorbitol on EOH medium in order to suspect pathogenic E.coli O157 colonies. The results show that coliform contamination was 1.103 - 1.107 CFU/ml, although it was not detected on all of the samples. Profile of coliform contamination in fresh milk samples consisted of Citrobacter, Enterobacter, and Klebsiella (1,0.103  - 1,2.107 CFU/ml), Shigella, Salmonella, and Yersinia (1,0.103 - 2,1.106 CFU/ml), and E.coli (1,4.104 - 2,8.104 CFU/ml). Dark-blue isolates that were suspected as pathogenic E.coli do not ferment D-sorbitol on EOH medium. Based on this result, it was concluded that it was not associated with E.coli O157.